Hadith #2682 - Sunan Abi Dawud - Asbat bin Nsr al-Hmdany أسباط بن نصر الهمداني; Mus'ub bin Sa'd ibn Abi Waqqas مصعب بن سعد بن أبى وقاص الزهرى; Sa'd ibn Abi Waqqas; Uthman bin Muhammad (Sunan Abi Dawud)
When the children of a woman (in pre-Islamic days) did not survive, she took a vow on herself that if her child survives, she would convert it a Jew. When Banu an-Nadir were expelled (from Arabia), there were some children of the Ansar (Helpers) among them. They said: We shall not leave our children. So Allah the Exalted revealed; “Let there be no compulsion in religion. Truth stands out clear from error.” Abu Dawud said: Muqlat means a woman whose children do not survive.
Grade: Sahih

Hadith #3040 - Sunan Abi Dawud - Asbat bin Nsr al-Hmdany أسباط بن نصر الهمداني; ibn Abbas; Masraf bin 'Amr bin al-Sari مصرف بن عمرو بن السري; Yunus bin Bukayr al-Shaybani يونس بن بكير بن واصل الشيباني (Sunan Abi Dawud)
‘Ali said “If I survive for the Christians of Banu Taghlib I shall kill fighters and captivate children for I had written a document between them and the Prophet(ﷺ) to the effect that they would not make their children Christian. Abu Dawud said “This is rejected (munkar) tradition and it has reached me from Ahmad (bin Hanbal) that he used to reject this tradition seriously. Abu ‘Ali said “Abu Dawud did not present this (tradition) in this second reading.”
Grade: Da'if

Hadith #4357 - Sunan Abi Dawud - Asbat bin Nsr al-Hmdany أسباط بن نصر الهمداني; Mus'ub bin Sa'd ibn Abi Waqqas مصعب بن سعد بن أبى وقاص الزهرى; Sa'd ibn Abi Waqqas; Uthman bin Muhammad (Sunan Abi Dawud)
The tradition mention above has also been transmitted by Abu Musa through a different chain if narrators. But there is no mention of demand of repentance.
Grade: Da'if

Hadith #150 - Sunan Ibn Majah - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Asbat bin Nsr al-Hmdany أسباط بن نصر الهمداني; Isma'il bin 'Abdur Rahman al-Saddi إسماعيل بن عبد الرحمن السدي; Muhammad bin Matraf محمد بن مطرف; Zayd bin Arqam (Sunan Ibn Majah)
“I saw the Messenger of Allah performing ablution, washing each part three times, and wiping his head once.”
Grade:

Hadith #1894 - Sunan Ibn Majah - Ady bin Thabit al-Ansari عدي بن ثابت الأنصاري الكوفي; Ahmed bin Muhammad bin Yahya أحمد بن محمد بن يحيى; al-Bara' bin Azib bin al-Harith; Amr bin Muhammad al-Anqazi عمرو بن محمد العنقزي; Asbat bin Nsr al-Hmdany أسباط بن نصر الهمداني; Isma'il bin 'Abdur Rahman al-Saddi إسماعيل بن عبد الرحمن السدي (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade the price of a dog and studding a stallion.”
Grade: